The comparative analysis of discretionary accruals viewed from the styles of audit and IFRS adoption - Sulhani Sulhani; Hangga Darisman (Universitas Hayam Wuruk Perbanas, 2015)
Discretionary accruals in auditing have been the essential factor. Therefore, an analysis of this factor viewed from different styles of audit and IFRS adoption can be more interesting to study. This study discusses financial statement comparabil-ity in terms of audit style and IFRS adoption. It took the sample consisting of 43 manufacturing companies listed in Indonesia Stock Exchange; all have published their financial statements for the period of 2010-2013. The data were analyzed by using Kruskal-Wallis test and Wilcoxon test. The results showed that financial statement with the same accounting standards and audited by the same big 4 auditors, subject to the same audit style, are more likely to have comparable dis-cretionary accruals than financial statement audited by different Big 4 firms with different styles. By comparable, it means that different financial statements in the same industry and the same accounting standard will have more similar discre-tionary accruals.